Percentage of using formulaic language in media discourseA comparison between the visual media and the written press: language - Ahmed, Shorashvan A. (Humanities Journal of University of Zakho, 2024)
the language we use daily; A product of society, but each of us embodies it in his way. Therefore, the speaker produces the language, but there is another aspect of the language, which is ready-made linguistic pieces, used directly by the individual owned by the linguistic group. Formulaic language is a general term for ready-made phrases in the language that have previously been produced and stored in human memory. This language usually has a fixed grammatical formula and a special meaning according to the situation and context in which it is presented. The use of this language leads to the coordination of sentences in the process of writing and communication, as well as adopting the eloquence of the sender and can influence the recipient more and convince him of his ideas, as well as help in logical intentions, automatic translation, and smart answers. This research, titled "Percentage of using formulaic language in media discourse: A comparison between the visual media and the written press", sheds light on the intensity of the formal language in the visual media and the written press. In the beginning, the formulaic language was explained, and then its use in the Kurdish media was explained. The importance of research in linking the media discourse with formal language, the purpose of which is to know the percentage of using this language on the one hand, and on the other hand, to know the percentage of its use between the two types. To conduct the research, (18) interviews and articles were taken from the visual media and the written press. After that, six components of the grammatical language were extracted, which are (linguistic accompaniment, coins (expressions), metaphor, proverbs, phrasal verbs, and lexical expressions) according to (Wadi), and the use of each one of them was indicated in a table.